Megasari, Ita IMPLEMENTASI AUDIT OPERASIONAL UNTUK MENINGKATKAN EFEKTIVITAS DAN EFISIENSI PENGENDALIAN INTERNAL PADA ORGANISASI NIRLABA (Nsc Press, 2016)
This study aims to determine how the operational audit applied to the Unit Study Group University â€œXâ€, thus helping the management in solving various problems faced and provide recommendations for improvements required by the organization. This study is a qualitative study using a case study approach. Operational audit is done through 4(four) stages, namely a preliminary survey to gain an overview of the organization in general, then do the analysis and verification of the evidence, evaluating the results of the audit, and the last stage is to report the results of the audit. The results of this study indicate that the internal control system at Unit Study Group Universityâ€œXâ€is still need for improvement, namely the need to complete the organizational structure to the job description, the internal control of the supporting evidence, making policy in writing related to calculation of salary expenditure implementing the project, to resume cooperation networks with the mediato improve the image Unit Study Group-Universityâ€œXâ€, as well as adding staff to assist in the areas of administration and finance.